Dangerous crossing: demographic and clinical features of rescued sea migrants seen in 2014 at an outpatient clinic at Augusta Harbor, Italy. Issue 1 (December 2016) - Trovato, Alessia; Reid, Anthony; Takarinda, Kudakwashe; Montaldo, Chiara; Decroo, Tom; Owiti, Philip; Bongiorno, Francesco; Di Carlo, Stefano
Abstract Background In recent years Europe has received an increasing influx of migrants, many of whom risked their lives crossing the Mediterranean Sea. In October 2013, Italy launched a search and rescue operation at sea in response to migrant deaths during the sea crossing. In August 2014, Médecins sans Frontières and the local Ministry of Health established an outpatient clinic at Augusta harbor, in Sicily, which received 26 % of total sea migrants arrived in Italy in 2014, to provide immediate medical assessment and care. Methods This is a descriptive study of demographic and clinical data of sea migrants seen at the port clinic in Augusta from August to December 2014. We compared migrants from Near Eastern, war-torn regions (Group 1) and the others, mostly African (Group 2), as there were significant differences in terms of demographic and morbidity profiles. Results There were 2593 migrants consulting the clinic (17 % af all rescued migrants) with 5 % being referred to hospital. Most were young males. The overall burden of vulnerability (pregnant women, children ≤5 years, unaccompanied minors, single parents with children of minor age, disabled and elderly persons) was 24 %. There were more small children, pregnant women, elderly, disabled, and persons with chronic diseases in Group 1, as compared to Group 2. Group 2 had more unaccompanied minors. Morbitidies in common were respiratory, dermatological, trauma-related and gastrointestinal conditions. However, acute and chronic cardiovascular disease, as well as diabetes, were more frequent in Group 1; chronic diseases affected 19 % of this group. Group 2 had more patients with skin diseases. Most migrants attributed their presenting symptoms to the perils of their journey. No risks for public health were detected. Conclusion Among sea migrants, we identified two groups with different demographic and clinical characteristics, as well as vulnerability patterns. Overall morbidity suggested that the dangerous journey affected migrants' health. Medical activities at reception sites should include screening for vulnerability and chronic disease management. Ensuring medical care to migrants on arrival can address European humanitarian obligations and provide support to local medical facilities.